Síntese de novos híbridos moleculares a partir de um derivado da piperina e anéis tetraidropiranos com potencial atividade antinociceptiva - Almeida, Thiago Brito de (2014)
This work was presented using the technique of molecular hybridization which is a classic strategy in medicinal chemistry and useful in the design of new drugs, consisting of the covalent joining of two or more fragments known pharmacophoric or already present recognized therapeutic activities. Described the technique of extraction, isolation and purification of piperine 6 with 2% yield, with the same natural molecule mostly present in black pepper, where studies have shown a variety of biological activities as analgesic, anti-inflammatory, anti-thermal, antitumor, antifungal, antichagasic, insecticide, leishmanicidal, among others. Next, was performed the synthesis of the respective piperic acid 12 obtained via basic hydrolysis with 87% yield. A series of alcohols tetrahydropyran derivatives replaced (33, 34, 37, 38, 79 and 80) were synthesized in good yields (76% -100%), with synthetic route and potent antinociceptive already described by our group research. The Prins cyclization reaction was used as key step to build diastereoselective 2,4-cis and 2,4,6-cis tetrahydropyranyl rings. Subsequently, we performed the synthesis of 6 novel hybrid molecules (64, 65, 66, 67, 68 and 69), based on the structure of an analog of piperine (piperic acid) with 6 alcohols substituted tetrahydropyran derivatives, using the classical approach molecular hybridization by Steglich esterification reaction to join the two portions with relatively good yields (42% - 78%), which was the intention enhance the analgesic activity by these two chemical entities. All molecular hybrids were characterized by spectroscopic (1H and 13C) and IR